Determination of the phytotochemical profile and evalution of biological activities of leaf extracts of Ilex brevicuspis Reissek. (Aquifoliaceae) (Research, Society and Development, 2021)
The genus Ilex comprises about 500 species being considered a promising source for the extraction of active principles with different biological activities. Before this approach, this work used Ilex brevicuspis Reissek leaves for the production of extracts, aiming the phytochemical, antioxidant, antimicrobial and acaricide determination in Dermanyssus gallinae (Degeer, 1778). The leaves were collected, dried and ground in a mill, and their extracts produced with different solvents: ethanol (EE), methanol (EM), ethyl EAEate (EAE) and water (Eaq). Phytochemical analyses revealed three groups of compounds: saponins, steroids and tannins. The extracts showed inhibitory and bactericidal activity for standard strains (Gram-negative and positive) and for ten serotypes of Salmonella spp. The EM extract showed the best MIC results for the standard strains, ranging from 6.25 mg/mL to 50 mg/mL and for MBC from 6.25 mg/mL to 100 mg/mL. For serotypes of Salmonella, EE extract presented the best activity, varying from 25 mg/mL to 50 mg/mL for MIC and 200 mg/L for MBC. EM extract showed a high acaricidal activity of 94% and moderate antioxidant capacity of 81.45%. Assays demonstrated that EM and EE extracts of I. brevicuspis represent an alternative potential for the control of bacteria and mites, demonstrating a new perspective for the future development of natural products from a native species.